Relationship between [123I]‐FP‐CIT SPECT and clinical progression in Parkinson's disease. (3rd June 2016) - Ramani, L.; Malek, N.; Patterson, J.; Nissen, T.; Newman, E. J.
Abstract : Background: The demonstration of presynaptic dopaminergic deficiency on [ 123 I]‐FP‐CIT SPECT imaging is a useful ancillary tool in the diagnosis of Parkinson's disease (PD). Whilst there is evidence of a cross‐sectional relationship between the degree of dopaminergic deficiency and severity of bradykinesia and rigidity, longitudinal studies are rare. Moreover, the relationship between motor subtypes and their dopaminergic deficient state is not well characterized. Aim: Our primary aim was to assess the correlations between dopaminergic deficiency on baseline [ 123 I]‐FP‐CIT SPECT imaging with the progression of motor severity in patients classified by motor subtype, and the development of motor complications. Our secondary aim was to assess the correlation between UPDRS‐III subscores and the time to onset of motor complications. Methods: 42 PD patients with abnormal baseline [ 123 I]‐FP‐CIT SPECT scans and at least 3 years of clinical follow‐up were classified by motor subtype: akinetic–rigid, tremor‐dominant or mixed. UPDRS‐III scores at baseline and at 3‐year follow‐up, and time to onset of motor complications were recorded. Results: [ 123 I]‐FP‐CIT uptake ratios were inversely correlated with UPDRS‐III scores at 3 years only in akinetic–rigid patients ( r =−.51, P =.04). Time to onset of motor complications was inversely correlated with UPDRS‐III subscores for bradykinesia and rigidity at baseline ( r =−.52, P =.02) and at 3 years ( r =−.54, P =.01). Conclusion: The degree of dopaminergic deficiency on baseline [ 123 I]‐FP‐CIT SPECT inversely correlates with motor severity at 3‐year follow‐up in akinetic–rigid patients only. Furthermore, UPDRS‐III subscores for bradykinesia and rigidity at baseline show an inverse correlation with time to onset of motor complications across all PD subtypes.